On the existence of low-valent magnesium-calcium complexes - Mai, Jonathan; Rösch, Bastian; Patel, Neha; Langer, Jens; Harder, Sjoerd (Chemical Science, 2023)
DFT-Calculations predict that a low-valent complex (BDI)Mg-Ca(BDI) with bulky beta-diketiminate (BDI) ligands is thermodynamically stable. It was attempted to isolate such a complex by salt-metathesis between [((BDI)-B-DIPeP*) Mg-Na+](2) and [((BDI)-B-DIPeP)CaI](2) ((BDI)-B-DIPeP = HC[C(Me)N-DIPeP](2); (BDI)-B-DIPeP* = HC [C(tBu)N-DIPeP](2); DIPeP = 2,6-CH(Et)(2)-phenyl). Whereas in alkane solvents no reaction was observed, salt-metathesis in C6H6 led to immediate C-H activation of benzene to give ((BDI)-B-DIPeP*) MgPh and ((BDI)-B-DIPeP) CaH, the latter crystallizing as a THF-solvated dimer [((BDI)-B-DIPeP) CaHTHF](2). Calculations suggest reduction and insertion of benzene in the Mg-Ca bond. The activation enthalpy for the subsequent decomposition of C(6)H(6)2(-) into Ph- and H- is only 14.4 kcal mol(-1). Repeating this reaction in the presence of naphthalene or anthracene led to heterobimetallic complexes in which naphthalene(2-) or anthracene(2-) anions are sandwiched between ((BDI)-B-DIPeP*)Mg+ and ((BDI)-B-DIPeP)Ca+ cations. These complexes slowly decompose to their homometallic counterparts and further decomposition products. Complexes in which naphthalene(2-) or anthracene(2-) anions are sandwiched between two ((BDI)-B-DIPeP)Ca+ cations were isolated. The low-valent complex (BDI)-B-(DIPeP*)Mg-Ca((BDI)-B-DIPeP) could not be isolated due to its high reactivity. There is, however, strong evidence that this heterobimetallic compound is a fleeting intermediate.
CRIS-Team WoS Importer:2023-05-26